Persepsi Guru SD tentang Pemanfaatan Deep Learning untuk Meningkatkan Literasi Digital Siswa - Atalya Cherin Dwi Hamber; Jamalri Pajow; Aurike Aneke Novita Korua; Iryanti Sili; Widdy H. F. Rorimpandey (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to describe elementary school teachers’ perceptions of the use of deep learning in enhancing students’ digital literacy. The research employed a qualitative approach with a case study design conducted at SD Negeri 2 Tomohon. The research participants consisted of elementary school teachers selected through purposive sampling based on their involvement in technology-integrated learning activities. Data were collected through classroom observations, in-depth interviews, and document analysis. The data were analyzed using qualitative data analysis procedures, including data reduction, data display, and conclusion drawing. The findings indicate that teachers generally hold positive perceptions of deep learning as a learning approach that promotes deeper conceptual understanding, increases student engagement, and supports the development of digital literacy skills. However, the implementation of deep learning at the elementary school level still encounters several challenges, such as limited teachers’ conceptual understanding, differences in students’ digital competencies, and inadequate supporting facilities. Despite these challenges, teachers believe that the integration of deep learning with digital technology has the potential to improve the quality of learning when supported by continuous professional development and appropriate school policies. This study contributes to the growing body of research on teachers’ perceptions of technology-based instructional innovations in elementary education.